Long film, method for producing long film, method for producing long laminate, and long laminate

JP7639682B2Active Publication Date: 2025-03-05AGC INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021530693
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-28
Filing Date
2020-07-07
Publication Date
2025-03-05
Estimated Expiration
2040-07-07

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、密着性と高温安定性とに優れた長尺フィルム及び長尺積層体、好適には、はんだ耐熱性に優れ、剥離が生じにくいプリント配線板を製造し得る長尺フィルム及び長尺積層体が得られる。また、本発明によれば、熱衝撃性に優れ、断線が生じにくいプリント配線板を製造し得る長尺フィルム及び長尺積層体も得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639682000004
    Figure 0007639682000004
  • Figure 0007639682000005
    Figure 0007639682000005
  • Figure 0007639682000006
    Figure 0007639682000006
Patent Text Reader

Abstract

The present invention provides: a specific long film; a method for producing this long film; a method for producing a long multilayer body which uses this long film; and a long multilayer body. One example of a long film according to the present invention is configured of a thermofusible polymer that contains a first unit based on tetrafluoroethylene and a second unit based on perfluoro(alkyl vinyl ether), and contains spherulites of the thermofusible polymer, said spherulites having a radius of 10 μm or less. Another example of a long film according to the present invention is configured of a tetrafluoroethylene polymer having a melt flow rate of from 5 g / 10 minutes to 40 g / 10 minutes; and if the thermal expansion and contraction ratio of the long film is measured by heating the long film at 180°C for 30 minutes, and A is the thermal expansion and contraction ratio in a first direction that is at an angle of 45° to the flow direction of the long film and B is the thermal expansion and contraction ratio in a second direction that is perpendicular to the first direction, A and B are respectively from -2% to +1% and |A - B| is 1% or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a specified long film, a method for producing the long film, a method for producing a long laminate using the long film, and the long laminate. [Background technology]

[0002] Laminates of fluororesin films and other substrates take advantage of the properties of fluororesins (heat resistance, electrical properties, chemical resistance, etc.) and are used in printed wiring boards, electromagnetic shielding sheets, exterior bodies for lithium ion batteries, etc. Such laminates are produced by superposing a fluororesin film on the surface of a supporting substrate such as a metal foil or a polyimide film, and laminating it with a heated roll (see Patent Documents 1 and 2). Patent documents 1 and 2 both describe a method in which a fluororesin film is temporarily laminated onto a polyimide film to obtain a temporary laminate, and then a metal foil (or a copper-clad laminate) is permanently laminated onto this temporary laminate to obtain a long laminate. Patent Document 2 also describes the preferred thermal expansion and contraction rate in the machine direction (MD) and the preferred thermal expansion and contraction rate in the direction perpendicular to the machine direction (TD) of a tetrafluoroethylene-based polymer film used in the production of a long laminate. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-087799 A [Patent Document 2] International Publication No. 2019 / 008876 Summary of the Invention [Problem to be solved by the invention]

[0004] The present inventors have found that in such a provisional laminate, the fluororesin film and the support substrate are sufficiently adhered to each other macroscopically, but are not necessarily sufficiently adhered to each other microscopically, and partial voids may be observed. In addition, the present inventors have found that if the size of the voids is large at the stage of the provisional laminate, partial peeling or voids are likely to occur between the two due to heating in the actual lamination. Furthermore, the present inventors have found that when the obtained long laminate is exposed to a high-temperature atmosphere, the peeling between the two is likely to progress further starting from the partial peeling or voids. The present inventors believed that these problems were caused by steps (unevenness) at the boundary between the crystalline and amorphous parts of the fluororesin film surface, and conducted extensive research. As a result, they found that by setting the size of the spherulites of the fluoropolymer that constitutes the fluororesin film within a certain range, peeling and the occurrence of voids can be suppressed in the temporary laminate or long laminate. An object of the present invention is to provide a long film containing small-sized spherulites and a method for producing the same, as well as a method for producing a long laminate using such a long film and the long laminate.

[0005] The inventors have also found that the distortion remaining in a tetrafluoroethylene-based polymer film is complex, and in particular, in such a film, distortion remains in an oblique direction inclined to the flow direction due to the bowing phenomenon during film formation, resulting in non-uniform thermal shrinkage in the oblique direction. It has also been found that when a long laminate is manufactured from such a film having a non-uniform thermal expansion rate in the oblique direction, wrinkles occur due to the distortion in the oblique direction, and the yield rate decreases. Furthermore, it has been found that when a long laminate is manufactured from such a film, the distortion in the oblique direction is also maintained in the long laminate, its thermal shock resistance decreases, and it becomes easy to deform in the oblique direction when it is processed. Another object of the present invention is to provide a long film in which the thermal expansion and contraction rates in two oblique directions and the difference between them are set within predetermined ranges, a method for producing the same, and a method for producing a long laminate using such a long film. [Means for solving the problem]

[0006] <1> A long film comprising a heat-fusible polymer containing a first unit based on tetrafluoroethylene and a second unit based on perfluoro(alkyl vinyl ether), the film containing spherulites of the heat-fusible polymer, the spherulites having a radius of 10 μm or less. <2> The heat-fusible polymer further contains a third unit based on a monomer having a polar functional group. <1> A long film. <3> The heat-fusible polymer contains, as the second unit, 2 to 4 mol % of a unit based on perfluoro(propyl vinyl ether). <1> or <2> A long film. <4> The melt flow rate of the heat-fusible polymer is 5 to 40 g / 10 min. <1> ~ <3> A long film. <5> The haze of the long film having a thickness of 50 μm is 1 to 5%. <1> ~ <4> Any of the long films. <6> <1> ~ <5> The long film manufacturing method according to any one of the above items 1 to 5 is manufactured by a die coating method, in which the heat-fusible polymer is discharged in a molten state from a die, and the molten heat-fusible polymer is heated by a non-contact heating section before contacting with a first cooling roll. <7> When the temperature of the heat-meltable polymer in the die is defined as X and the temperature of the first cooling roll is defined as Y, XY is 230° C. or more. <6> Manufacturing method. <8> When the temperature of the heat-meltable polymer in the die is defined as X and the temperature of the non-contact heating part is defined as Z, |XZ| is 70° C. or less; <6> or <7> Manufacturing method. <9> <1> ~ <5> and a long substrate at a temperature of 25 to 100° C. to obtain a long laminate having the long film and the long substrate in this order. <10> <1> ~ <5> and a conductive metal layer in this order. <11> A long film made of a tetrafluoroethylene polymer having a melt flow rate of 5 to 40 g / 10 min, the long film being heated at 180°C for 30 minutes to measure its thermal expansion / contraction rate, where A is the thermal expansion / contraction rate in a first direction that forms an angle of 45° with the flow direction and B is the thermal expansion / contraction rate in a second direction perpendicular to the first direction, and A and B are each -2 to +1%, and |AB| is 1% or less. <12> The tetrafluoroethylene-based polymer is a tetrafluoroethylene-based polymer having a polar functional group. <11> A long film. <13> <11> or <12> The long film of claim 1 is produced by a die coating method, the long film being produced by extruding the tetrafluoroethylene-based polymer in a molten state from a die, and heating the molten tetrafluoroethylene-based polymer in a non-contact heating section before the polymer comes into contact with a first cooling roll. <14> When the temperature of the tetrafluoroethylene-based polymer in the die is defined as X and the temperature of the non-contact heating part is defined as Z, |XZ| is 70° C. or less; <13> Manufacturing method. <15> <11> or <12> The long film and the long substrate are laminated at a temperature of 25 to 100° C. to obtain a long laminate having the long film and the long substrate in this order. Effect of the Invention

[0007] According to the present invention, it is possible to obtain a long film and a long laminate having excellent adhesion and high-temperature stability, preferably a long film and a long laminate capable of producing a printed wiring board having excellent solder heat resistance and being resistant to peeling. Also, according to the present invention, it is possible to obtain a long film and a long laminate capable of producing a printed wiring board having excellent thermal shock resistance and being resistant to breakage. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic diagram showing one embodiment of a long film production apparatus used in Methods 1 and 3. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of a manufacturing apparatus for a long laminate used in Methods 2 and 4. [Diagram 3] FIG. 1 is a schematic diagram showing another embodiment of the apparatus for producing a long laminate used in Methods 2 and 4. [Figure 4] 1 is a photograph of the surface of a long film 12 observed with a polarizing microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The following terms have the following meanings. The term "thermofusible polymer" refers to a polymer that exhibits melt fluidity, and refers to a polymer that has a melt flow rate of 0.1 to 1000 g / 10 min at a temperature that is 20° C. or more higher than the melting temperature of the polymer under a load of 49 N. "Melt flow rate (MFR)" means the melt mass flow rate of a polymer as defined in JIS K 7210:1999 (ISO 1133:1997). The "melting temperature (melting point) of a polymer" is the temperature corresponding to the maximum value of the melting peak of the polymer as measured by differential scanning calorimetry (DSC). The "water absorption rate of the substrate" is a value measured by the method specified in ASTM D570, and specifically, is the rate of weight change before and after immersing the substrate in water at 23° C. for 24 hours. "Ten-point average roughness of the substrate surface (Rzjis)" is a value specified in Appendix JA of JIS B 0601:2013. The "unit" in a polymer may be an atomic group formed directly from a monomer by a polymerization reaction, or may be an atomic group in which a part of the structure is converted by treating a polymer obtained by a polymerization reaction with a predetermined method. A unit based on monomer A contained in a polymer is also simply referred to as a "monomer A unit". "(Meth)acrylate" is a general term for acrylate and methacrylate.

[0010] The long film according to the first embodiment of the present invention (hereinafter also referred to as "film 1") is composed of a heat-fusible F polymer containing a first unit based on TFE and a second unit based on perfluoro(alkyl vinyl ether) (PAVE). Film 1 contains spherulites of the F polymer, and the radius of the spherulites (hereinafter also referred to as "spherulite radius") is 10 μm or less. In the present film 1 containing such small spherulites, the size of the step (irregularity) at the boundary between the crystalline part (spherulite part) and the amorphous part present on the surface is sufficiently small, in other words, it is considered that the surface is sufficiently smooth. Therefore, in a laminate (provisional laminate) formed by laminating a long substrate on the present film 1, the adhesion between the present film 1 and the long substrate is high, and it is considered that microscopic voids are unlikely to form between them.

[0011] That is, in the temporary laminate, it is considered that no gaps are formed between the present film 1 and the long substrate, or even if gaps are formed, their size is sufficiently small. Therefore, it is believed that partial peeling between the present film 1 and the long substrate and the occurrence of voids can be suppressed in the laminate (the present laminate) obtained by laminating a second long substrate onto such a temporary laminate while heating it. For example, this laminate using a long metal foil on at least one of the long substrate and the second long substrate (hereinafter collectively referred to as "long substrate") can be suitably used as a printed wiring board by cutting it to a predetermined length and processing the metal foil into a transmission circuit. Even when such a printed wiring board is subjected to a solder heat resistance test, the above-mentioned partial peeling and peeling that progresses from voids are likely to be prevented. In other words, by using this film 1, a printed wiring board (or this laminate) with excellent solder heat resistance can be easily obtained.

[0012] The F polymer in the present film 1 includes at least one type of heat-fusible F polymer. The spherulite radius of the F polymer contained in the present film 1 is 10 μm or less, preferably 7.5 μm or less, and more preferably 5 μm or less. In this case, the adhesion between the present film 1 and the long substrate is more likely to be improved. The spherulite radius is preferably 0.2 μm or more, and more preferably 0.5 μm or more. The MFR of the F polymer in the present film 1 is preferably 5 to 40 g / 10 min, more preferably 10 to 30 g / 10 min, and even more preferably 15 to 30 g / 10 min, in which case the spherulite radius of the F polymer is easy to control. The melting temperature of the F polymer in the present film 1 is preferably 200 to 320° C. In this case, the yield during the production of the present film 1 is further improved.

[0013] The F polymer in the present film 1 is a copolymer containing a first unit based on TFE and a second unit based on PAVE. The proportion of the first unit and the proportion of the second unit in all units constituting the F polymer are preferably 80 to 99 mol % and 1 to 20 mol %, respectively. The F polymer may further contain other units. The F polymer may also contain a polar functional group, which will be described later, in the main chain terminal group. Examples of PAVE include perfluoro(methyl vinyl ether) (CF2=CFOCF3: PMVE), CF2=CFOCF2CF3, perfluoro(propyl vinyl ether) (CF2=CFOCF2CF2CF3: PPVE), and CF2=CFOCF2CF2CF2CF3. The F polymer in the present film 1 is preferably (i) an F polymer further containing a third unit based on a monomer having a polar functional group, (ii) an F polymer containing 2 to 4 mol % of PPVE units as the second units, or (iii) an F polymer containing PMVE units as the second units.

[0014] In the F polymer of (i) above, the polar functional groups interact with each other during crystallization, which promotes the formation of a lamellar structure and is believed to facilitate the convergence of the spherulite radius to a desired range in the present film 1. In addition, the polar functional groups tend to further increase the adhesion of the present film 1 to a long substrate. The polar functional group is preferably a hydroxyl group-containing group, a carbonyl group-containing group, an acetal group or a phosphono group (-OP(O)OH2), and from the viewpoint of further improving the adhesion to the long substrate, a carbonyl group-containing group is more preferable.

[0015] The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, and more preferably -CF2CH2OH, -C(CF3)2OH or a 1,2-glycol group (-CH(OH)CH2OH). The carbonyl group-containing group is a group containing a carbonyl group (>C(O)), and is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.) or a carbonate group (-OC(O)O-).

[0016] Among all the units constituting the F polymer of (i) above, the proportion of the first units, the proportion of the second units, and the proportion of the third units are preferably 90 to 99 mol %, 0.5 to 9.97 mol %, and 0.01 to 3 mol %, respectively. Examples of the monomer constituting the third unit include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride (also known as himic anhydride; hereinafter also referred to as "NAH"), and maleic anhydride.

[0017] The F polymer (ii) above contains a medium amount (2 to 4 mol%) of PPVE units as second units, which is thought to promote the formation of a lamellar structure during crystallization and facilitate the convergence of the spherulite radius in the present film 1 to a desired range. This F polymer is composed of TFE units and PPVE units, and preferably contains 96 to 98 mol% of TFE units and 2 to 4 mol% of PPVE units. It is believed that the F polymer (iii) above contains PMVE units with short side chains as second units, which promotes the formation of a lamellar structure during crystallization, and the spherulite radius in this film 1 converges to the desired range. This F polymer preferably contains 10 to 20 mol % of PMVE units. This F polymer is composed of TFE units and PMVE units, and preferably contains 80 to 90 mol % of TFE units and 10 to 20 mol % of PPVE units.

[0018] The F polymer in the present film 1 may be used alone or in combination with two or more kinds. The latter embodiment includes an embodiment including a first F polymer containing less than 2 mol% of PPVE units as second units, and a second F polymer selected from the group consisting of the F polymer (iii) and the F polymer (i). In this embodiment, it is believed that the second F polymer functions as a crystal nucleus, and the crystallization of the first F polymer is promoted around this crystal nucleus, making it easy to adjust the spherulite radius of the present film 1 to a desired range. The first F polymer consists of TFE and PPVE units, and preferably contains more than 98 mol % TFE units and less than 2 mol % PPVE units. The ratio by mass of the first F polymer to the second F polymer is preferably 2 to 50, more preferably 5 to 35. In this case, it is easier to adjust the spherulite radius of the F polymer.

[0019] In the present film 1, the size of the spherulites (spherulite radius) of the F polymer is sufficiently small. Therefore, the haze of the present film 1 is reduced. Specifically, when the present film 1 having a thickness of 50 μm is produced, the haze is preferably 1 to 5%, and more preferably 1 to 3%. Note that, by adjusting the content of the second unit in the F polymer to the above range, the size of the spherulites can be made sufficiently small, and the haze can be controlled to a range of 1 to 5%. In this case, the present film 1 can also be provided with excellent heat resistance. The present film 1 may contain a resin other than the F polymer as long as the effect of the present invention is not impaired. However, the amount of the F polymer contained in the present film 1 is preferably 90% by mass or more, and more preferably 100% by mass.

[0020] Examples of resins other than F polymer include epoxy resins, polyimide resins, polyamic acids which are polyimide precursors, acrylic resins, phenolic resins, liquid crystalline polyester resins, polyolefin resins, modified polyphenylene ether resins, polyfunctional cyanate ester resins, polyfunctional maleimide-cyanate ester resins, polyfunctional maleimide resins, vinyl ester resins, urea resins, diallyl phthalate resins, melamine resins, guanamine resins, melamine-urea co-condensation resins, styrene resins, polycarbonate resins, polyarylate resins, polysulfones, polyarylsulfones, aromatic polyamide resins, aromatic polyetheramides, polyphenylene sulfides, polyaryletherketones, polyamideimides, and polyphenylene ethers.

[0021] In addition, the present film 1 may contain other components such as a thixotropic agent, an antifoaming agent, a silane coupling agent, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, a surface treatment agent, a viscosity adjusting agent, and a flame retardant, as long as the effects of the present invention are not impaired.

[0022] The present film 1 can be produced by a die coating method (melt extrusion method using a T-die) from the viewpoint of ease of adjusting the size of the spherulites of the F polymer. The present inventors have found that the degree of growth of the F polymer spherulites in the die coating method depends on the state (temperature, fluidity) of the molten F polymer and the cooling conditions, and is determined in particular by the difference between the temperature of the molten F polymer and the temperature of the cooling roll (quenching conditions). In other words, the present inventors have found that, according to the die coating method, if the state of the F polymer and the cooling conditions are appropriately set, the growth of the F polymer spherulites is suppressed and the spherulite radius converges to a predetermined range.

[0023] The manufacturing method of the present film 1 (hereinafter also referred to as "the present method 1") is a method of manufacturing the present film 1 by a die coating method, in which the F polymer is extruded in a molten state from a die, and the molten F polymer is heated in a non-contact heating section before it comes into contact with the first cooling roll. FIG. 1 is a schematic diagram showing one embodiment of a long film production apparatus used in Method 1. 1 includes a T-die 20, a pair of first cooling rolls (initial cooling rolls) 30 arranged vertically below the T-die 20 to face each other, a second cooling roll 40 arranged alongside the first cooling roll 30, a take-up roll 50 that takes up the long film 1 (the present film 1), and transport rolls 61, 62 and a nip roll 70 arranged between the take-up roll 50 and the second cooling roll 40. The manufacturing apparatus 10 also includes a pair of heaters (non-contact heating units) 80 arranged to face each other between the T-die 20 and the first cooling roll 30.

[0024] The F polymer is melted by heating in an extruder (not shown) connected to the T-die 20 and fed into the T-die 20. The molten F polymer is discharged from the lip 21 of the T-die 20 toward the first cooling roll 30. Next, the discharged molten F polymer is heated without contacting the heaters 80 as it passes between the pair of heaters 80, and is cooled as it passes while being pinched (nipped) between the pair of first cooling rolls 30. Furthermore, the F polymer is cooled by contacting the second cooling roll 40, and then is transported by transport rollers 61 and 62. Thereafter, the F polymer passes through a nip roll 70 and is then wound up as a long film 1 onto a winding roll 50 .

[0025] According to this configuration, the molten F polymer discharged from the T-die 20 is maintained at a high temperature by heating with the heater 80 even while reaching the first cooling roll 30. Therefore, the molten F polymer flowing down toward the first cooling roll 30 maintains a relatively high fluidity, and is unlikely to be stretched by its own weight or the tensile force of the first cooling roll 30. As a result, it is presumed that the growth of spherulites of the F polymer is suppressed by the rapid cooling by the first cooling roll 30 during film formation, and a long film 1 containing spherulites having the above-mentioned size (radius) is obtained. In particular, in the configuration shown in Fig. 1, the F polymer discharged from the T-die 20 is heated by the heater 80 from both sides in the thickness direction, so that the temperature uniformity in the thickness direction is high, and the effect of uniforming the growth of the above-mentioned spherulites is excellent. From the viewpoint of uniforming the growth of spherulites, it is preferable to configure the heater 80 so that the temperature in the width direction of the F polymer can also be made uniform. In this case, for example, the width of the heater 80 may be designed to be sufficiently larger than the length of the F polymer in the width direction.

[0026] When the temperature of the F polymer in the T-die 20 is defined as X [°C] and the temperature of the heater 80 is defined as Z [°C], the difference therebetween (absolute value: |XZ|) is preferably 70°C or less, more preferably 30 to 50°C. In this case, the temperature of the F polymer can be maintained sufficiently high until it reaches the first cooling roll 30 while preventing deterioration of the F polymer. On the other hand, when the temperature of the F polymer in the T-die 20 is defined as X [°C] and the temperature of the first cooling roll 30 is defined as Y [°C], the difference (XY) is preferably 230°C or more, more preferably 250 to 300°C. In this case, the difference between the temperature of the molten F polymer and the temperature of the first cooling roll 30 can be made sufficiently large. Therefore, the F polymer can be efficiently quenched, thereby suppressing the growth of spherulites and making their size sufficiently small, and deformation of the long film 1 due to insufficient cooling can also be suitably prevented. Specifically, Y is appropriately set according to X, and is preferably 50 to 100°C.

[0027] From the viewpoint of achieving uniform growth of spherulites during cooling by the first cooling roll 30, it is preferable to configure the first cooling roll 30 so that the temperature of the F polymer can be made uniform in the width direction. Therefore, the first cooling roll 30 is preferably configured to have a mechanism for passing a heat medium, and is preferably configured to have a dual mechanism for repeatedly passing the heat medium back and forth in the axial direction. The first cooling roll 30 is preferably configured as a metal roll with excellent heat conductivity. The temperature Y of the first cooling roll 30 means the temperature of the heat medium. The thickness of the F polymer in a molten state before contacting the first cooling roll 30 (thickness t in FIG. 1) is preferably 5 to 150 μm, more preferably 10 to 100 μm. In this case, the accuracy of heating by the heater 80 and cooling by the first cooling roll 30 is improved, making it easier to control the size of the spherulites.

[0028] If the ratio of the opening of the lip 21 of the T-die 20 to the thickness of the long film 1 to be finally obtained (draw ratio) is large, the molecular chain of the F polymer is strongly stretched, and the polymer molecules tend to be oriented. As a result, the spherulites tend to become larger. Therefore, the draw ratio is preferably 50 or less. Moreover, the peripheral speed of the first cooling roll 30 (peripheral speed S in FIG. 1) is also preferably 2 to 25 m / min, more preferably 5 to 20 m / min, from the viewpoint of suppressing unnecessary growth of spherulites. The temperature of the second cooling roll 40 is preferably 30 to 80°C.

[0029] The F polymer (present film 1) after being separated from the first cooling roll 30 may be subjected to a surface treatment capable of introducing a polar functional group onto the surface. Examples of such surface treatments include discharge treatments such as corona discharge treatment and plasma treatment, plasma graft polymerization treatment, light irradiation treatments such as electron beam irradiation and excimer UV light irradiation, itro treatment using a flame, and wet etching treatment using metallic sodium. This surface treatment introduces polar functional groups such as hydroxyl groups, carbonyl groups, and carboxyl groups onto the surface of the long film 1, thereby improving adhesion to other surfaces.

[0030] 1, a pair of heaters 80 are provided, but only one may be provided. The non-contact heating unit may be configured with a blower device that blows hot air instead of the heater 80. Of the two first cooling rolls 30, the outer first cooling roll 30 may be omitted.

[0031] The film 1 can be used to produce a long laminate. The method for producing a long laminate of the present invention (hereinafter also referred to as "method 2") is a method in which the present film 1 and a long substrate are laminated at a temperature of 25 to 100°C to obtain a long laminate having the long film and the long substrate in that order. FIG. 2 is a schematic diagram showing one embodiment of an apparatus for producing a long laminate used in the present method 2. As shown in FIG. 2 has a pair of laminating rolls 101, and a first delivery roll 103 and a second delivery roll 105 (winding roll 50) that are spaced apart from each other and disposed upstream of the laminating rolls 101. The manufacturing apparatus 100 also has a winding roll (not shown) disposed downstream of the laminating rolls 101.

[0032] The laminating roll 101 is equipped with a heating mechanism, and the roll surface temperature can be adjusted to any temperature. Examples of rolls equipped with a heating mechanism include an electric heating roll, a heat medium circulating roll, and an induction heating roll. From the viewpoint of temperature uniformity throughout the roll, the laminating roll 101 is preferably an induction heating roll. The long substrate 2 is wound around the first delivery roll 103. The first delivery roll 103 controls the unwinding speed of the long substrate 2, and the tension applied to the long substrate 2 transported to the lamination roll 101 can be controlled. Meanwhile, the long film 1 (main film 1) is wound around the second delivery roll 105. The second delivery roll 105 controls the unwinding speed of the long film 1, and the tension applied to the long film 1 transported to the laminating roll 101 can be controlled.

[0033] In the manufacturing apparatus 100, the long substrate 2 continuously fed from the first feed roll 103 and the long film 1 continuously fed from the second feed roll 105 are superimposed between a pair of laminating rolls 101 having a surface temperature of T1, and are pressed in the thickness direction (lamination direction) at temperature T1 when continuously passing between the pair of laminating rolls 101. As a result, the long film 1 and the long substrate 2 are bonded together, and a long laminate L having them in this order is obtained. The obtained long laminate L may be continuously wound up by a winding roll machine in a subsequent stage, or may be directly subjected to the next step.

[0034] The surface temperature (lamination temperature) of the laminating roll 101, i.e., the temperature T1 during lamination of the long film 1 and the long substrate 2, is 25 to 100° C., preferably 35 to 80° C., and more preferably 45 to 60° C. In this case, it becomes easier to obtain an adhesive strength sufficient to prevent the long film 1 and the long substrate 2 from peeling off during transport of the long laminate L, and deformation of the long laminate L (particularly the occurrence of wrinkles in the long film 1) is suppressed. The surface temperature of the laminating roll 101 is a temperature measured on the surface of the laminating roll 101 by a contact thermocouple.

[0035] The pressure between the pair of laminating rolls 101, i.e., the pressure applied when laminating the long film 1 and the long substrate 2, is preferably 1 to 30 kN / m, and more preferably 5 to 20 kN / m. In this case, it becomes easier to obtain an adhesive strength sufficient to prevent the long film 1 and the long substrate 2 from peeling off during transport of the long laminate L, and deformation of the long laminate L (particularly the occurrence of diagonal wrinkles in the long film 1) is suppressed. The tension applied to each of the long film 1 and the long substrate 2 during transport is preferably set so as not to cause deformation of the long laminate L. Such tension is determined by a tension pickup roll. The tension applied to each of the long film 1 and the long substrate 2 can be adjusted by the first delivery roll 103 and the second delivery roll 105.

[0036] The running speed (lamination speed) at which the long film 1 and the long substrate 2 pass between the pair of lamination rolls 101 may be within a range in which the long film 1 and the long substrate 2 are well laminated, and is preferably set to 0.5 to 5 m / min. Furthermore, when the long film 1 and the long substrate 2 enter between the laminating rolls 101, the angle they form is preferably 3 to 45°. In this case, air between the long film 1 and the long substrate 2 during lamination can be suitably removed, and deformation of the long laminate L (particularly, occurrence of wrinkles in the long film 1) can be suppressed.

[0037] Furthermore, a second long substrate 3 may be laminated on the side of the long film 1 opposite to the long substrate 2. In this way, a long laminate M having a three-layer structure is obtained. Such a long laminate M can also be manufactured using a manufacturing apparatus 100 shown in Fig. 2. In Fig. 2, the reference characters in parentheses indicate the members in this step. In this case, in the manufacturing apparatus 100, a first delivery roll 103 around which the second long substrate 3 is wound and a second delivery roll 105 around which the long laminate L is wound are set so that the long film 1 of the long laminate L faces the second long substrate 3. The surface temperature (lamination temperature) of the lamination roll 101, i.e., the temperature T2 during lamination of the long laminate L and the second long substrate 3, is preferably above 100° C., and more preferably above 125° C. In this case, the long laminate L and the second long substrate 3 are easily bonded to each other sufficiently. Other conditions for laminating the long laminate L and the second long substrate 3, including the preferred embodiments and ranges thereof, can be set similarly to the conditions for laminating the long film 1 and the long substrate 2.

[0038] Each of the long substrate 2 and the second long substrate 3 preferably includes at least one of a long heat-resistant substrate and a long metal foil. Hereinafter, in the description relating to the heat-resistant substrate and the metal foil, the term "long" may be omitted. Examples of the heat-resistant substrate include a heat-resistant resin film, a woven or nonwoven fabric made of inorganic fibers, and a woven or nonwoven fabric made of organic fibers. Examples of heat-resistant resins include polyimides (such as aromatic polyimides), polyarylates, polysulfones, polyarylsulfones (such as polyethersulfones), aromatic polyamides, aromatic polyetheramides, polyphenylene sulfide, polyaryletherketones, polyamideimides, and liquid crystal polyesters.

[0039] Aromatic polyimide films are available in single-layer and multi-layer configurations. The former is commercially available as Kapton EN (manufactured by DuPont-Toray Co., Ltd.), while the latter is commercially available as Upilex VT and Upilex NVT (manufactured by Ube Industries, Ltd.), and Pixio BP (manufactured by Kaneka Corporation).

[0040] The polyimide film is preferably a polyimide film having a low water absorption rate. The polyimide constituting the polyimide film having a low water absorption rate is preferably a copolymer of paraphenyldiamine and 3,3'4,4'-biphenyltetracarboxylic dianhydride. The polyimide film having a low water absorption rate is preferably an aromatic polyimide film having no thermoplastic polyimide layer. An example of a commercially available liquid crystal polyester is BECSTAR CT-Z (manufactured by Kuraray Co., Ltd.). The water absorption rate of the heat-resistant substrate is preferably 2% or less, and more preferably 1.5% or less. A heat-resistant board is one that has a tensile modulus of elasticity of 1×10 at the lowest temperature of 260°C during the solder reflow process. 8 This means a substrate with a thermal conductivity of 10 Pa or higher. The thickness of the heat-resistant substrate is preferably from 5 to 150 μm, and more preferably from 12 to 75 μm.

[0041] The metal foil is appropriately selected depending on the application of the long laminate L, M. For example, when the long laminate L, M is used in an electronic device or an electric device, examples of the metal constituting the metal foil include copper, copper alloy, stainless steel, nickel, nickel alloy (including 42 alloy), aluminum, and aluminum alloy. Among these, the metal foil is preferably a copper foil, more preferably a rolled copper foil or an electrolytic copper foil, and even more preferably a rolled copper foil having no distinction between the front and back. The surface of the metal foil may be provided with an anti-rust layer (such as an oxide film of chromate or the like), a heat-resistant layer, a roughening treatment layer, or a silane coupling agent treatment layer.

[0042] The thickness of the metal foil is preferably from 2 to 40 μm, and more preferably from 2 to 15 μm. In addition, a carrier-attached metal foil containing two or more layers of metal foil may be used as the metal foil. The carrier-attached metal foil may be a carrier-attached copper foil consisting of a carrier copper foil (thickness: 10 to 35 μm) and an ultra-thin copper foil (thickness: 2 to 5 μm) laminated on the carrier copper foil via a release layer. By peeling off only the carrier copper foil of such a carrier-attached copper foil, a long laminate having an ultra-thin copper foil can be easily formed. By using this long laminate, it is possible to form a fine pattern by the MSAP (modified semi-additive) process, using the ultra-thin copper foil layer as a plating seed layer. A specific example of the metal foil with a carrier is "FUTF-5DAF-2" manufactured by Fukuda Metal Foil & Powder Co., Ltd.

[0043] The ten-point average roughness (Rzjis) of the surface of the metal foil is preferably 2 μm or less, more preferably 1 μm or less, and even more preferably less than 0.1 μm. The ten-point average roughness of the surface of the metal foil is preferably 0.01 μm or more. Even in the case of using such an extremely thin metal foil or a highly smooth metal foil with small surface roughness, a long film containing small spherulites (i.e., a long film with high surface smoothness) is used, so that a long laminate L, M having sufficient adhesiveness is easily obtained. In this case, the gap between the long film 1 and the metal foil becomes smaller, so that the printed wiring board obtained by processing the long laminate L, M has excellent electrical properties. When the long substrate 2 or the second long substrate 3 is a laminated substrate of a heat-resistant substrate and a metal foil, the heat-resistant substrate and the metal foil may be laminated directly or via an adhesive layer. Examples of the constituent material (adhesive) of the adhesive layer include thermoplastic polyimide and epoxy resin.

[0044] The long laminate M can be produced in two steps as described above, or can be produced in one step using the production apparatus shown in FIG. Fig. 3 is a schematic diagram showing another embodiment of the apparatus for producing a long laminate used in the present method 2. In Fig. 3, the same components as those in Fig. 2 are given the same reference numerals and detailed description thereof will be omitted. 3 has a pair of laminating rolls 101, and a first delivery roll 103, a second delivery roll 105, and a third delivery roll 107 that are spaced apart from each other and disposed upstream of the laminating rolls 101. The manufacturing apparatus 200 also has a take-up roll (not shown) disposed downstream of the laminating rolls 101. That is, the manufacturing apparatus 200 shown in FIG. 3 is similar to the manufacturing apparatus 100 shown in FIG.

[0045] 3, a long film 1 (main film 1) is wound around a first delivery roll 103. The first delivery roll 103 controls the unwinding speed of the long film 1, and thereby the tension applied to the long film 1 transported to the laminating roll 101 can be controlled. The long substrate 2 is wound around the second delivery roll 105. The second delivery roll 105 controls the unwinding speed of the long substrate 2, and the tension applied to the long substrate 2 transported to the lamination roll 101 can be controlled. In addition, the second long substrate 3 is wound around the third delivery roll 107. The third delivery roll 107 controls the unwinding speed of the second long substrate 3, and thereby the tension applied to the second long substrate 3 transported to the laminating roll 101 can be controlled.

[0046] In the manufacturing apparatus 200, the long film 1 continuously fed from the first feed roll 103, the long substrate 2 continuously fed from the second feed roll 105, and the second long substrate 3 continuously fed from the third feed roll 107 are superimposed between a pair of laminating rolls 101 having a surface temperature of T1, and are pressed in the thickness direction (lamination direction) at temperature T1 as they continuously pass between the pair of laminating rolls 101. As a result, the long substrate 2, the long film 1, and the second long substrate 3 are bonded together, and a long laminate M having these in this order is obtained. The obtained long laminate M may be continuously wound up by a winding roll machine in a subsequent stage, or may be directly subjected to the next step. The conditions for laminating the long substrate 2, the long film 1 and the second long substrate 3, including the preferred aspects and ranges thereof, can be set similarly to the conditions for laminating the long film 1 and the long substrate 2 in the description of FIG.

[0047] By using the above-mentioned manufacturing apparatuses 100 and 200, long laminates having various layer structures can be manufactured. Examples of such layer configurations include metal foil / long film, heat-resistant resin film / long film, metal foil / long film / metal foil, heat-resistant resin film / long film / heat-resistant resin film, long film / metal foil / long film, long film / heat-resistant resin film / long film, metal foil / long film / heat-resistant resin film / long film / metal foil. Note that "metal foil / long film" means that a metal foil and a long film are laminated in this order, and the same applies to other layer configurations.

[0048] The long laminate N having the last layer structure (i.e., a long laminate having a five-layer structure) can be manufactured by using a manufacturing apparatus 200 shown in Fig. 3, which is set with a first delivery roll 103 and a third delivery roll 107 around which a long laminate L having a metal foil and a long film 1 laminated thereon is wound, and a second delivery roll 105 around which a heat-resistant resin film 4 is wound, so that the long film 1 of the long laminate L faces the heat-resistant resin film 4. In Fig. 3, the reference characters in parentheses indicate the members in this process. In this case, the surface temperature (lamination temperature) of the laminating roll 101, i.e., the temperature T3 during lamination of the two long laminates L and the heat-resistant resin film 4, is preferably 250 to 450° C., more preferably 300 to 400° C. If the temperature T3 is within the above range, the long laminate L and the heat-resistant resin film 4 can be firmly bonded to each other. Other conditions for laminating the two long laminates L and the heat-resistant resin film 4 can be set similarly to the conditions for laminating the long film 1 and the long substrate 2, including the preferred embodiments and ranges thereof.

[0049] In addition, the long laminate N having the last layer structure described above can be produced by using the manufacturing apparatus 200 shown in Figure 3, which is equipped with a first delivery roll 103 and a third delivery roll 107 wound with metal foil, and a second delivery roll 105 wound with a long laminate M having a long film 1 laminated on both sides of a heat-resistant resin film. The lamination conditions in this case can be set similarly to the lamination conditions for the two long laminates L and the heat-resistant resin film 4 described above.

[0050] The long laminate formed from this film 1 comprises a long film composed of F polymer, and therefore has excellent physical properties such as heat resistance and electrical properties, making it useful as an electronic substrate material for printed wiring boards (especially flexible printed wiring boards). For example, a printed wiring board can be manufactured from the long laminate by cutting the long laminate to a predetermined length and etching the metal foil to process it into a transmission circuit of a predetermined pattern. Such a printed wiring board has a transmission circuit and an F polymer layer in this order, and since the F polymer layer is formed from a long film containing small-sized spherulites, it has excellent plating heat resistance and is unlikely to peel off from the transmission circuit and the F polymer layer.

[0051] Furthermore, a long laminate may be produced by forming a metal layer on the surface of the present film 1 using at least one of a vapor phase growth method and a plating method. Specifically, a metal seed layer is formed on the surface of the present film 1 using a vapor phase growth method, and then a metal layer is formed by a plating method, whereby a long laminate having the present film 1 and a conductive metal layer including the metal seed layer and the metal layer can be produced. The vapor deposition method may be a physical vapor deposition method or a chemical vapor deposition method.

[0052] Examples of metals constituting the metal layer include copper, copper alloys, stainless steel, nickel, nickel alloys (including alloy 42), titanium, titanium alloys, aluminum, and aluminum alloys. The thickness of the metal layer is preferably 1 to 20 μm, more preferably 3 to 15 μm. A metal layer of such a thickness can easily suppress the occurrence of warping in the entire laminate, making it suitable for use in various applications. Furthermore, vapor phase growth can easily form a uniform metal layer that has excellent adhesion to the present film 1. Examples of vapor phase growth can include sputtering, vacuum deposition, ion plating, and laser ablation, with sputtering being preferred. By using sputtering, a metal layer that has higher adhesion to the present film 1 can be formed. Specifically, the metal layer is preferably formed by forming a metal seed layer of nm order by a sputtering method, and then growing the metal layer to μm order by an electrolytic plating method. In the metal seed layer, it is preferable that the crystal structure of the metal forms a columnar structure.

[0053] The long laminate after the conductive metal layer is formed may be further heated and refired. In particular, when the long laminate after the conductive metal layer is formed is refired under a nitrogen gas atmosphere, the present film 1 is softened during heating, which makes it easier to improve the peel strength between the present film 1 and the conductive metal layer. In this case, the surface of the conductive metal layer diffuses into the present film 1 at a molecular level while suppressing the fluidity of the present film 1, making it easier to improve the peel strength between the conductive metal layer and the present film 1. In addition, refiring relieves the stress of the entire long laminate, making it easier to improve its dimensional stability.

[0054] Furthermore, before producing the long laminate, the present film 1 may be heat-treated to reduce the molding distortion. It is preferable that the absolute value of the rate of dimensional change in each of the MD (machine direction) and TD (transverse direction) when the film 1 is heated at 150°C for 30 minutes and then cooled to 25°C based on the dimensions at 25°C is less than 1.0%. In the normal form of the melt processable fluororesin film (roll film, etc.), the molding distortion resulting from the manufacturing method (melt molding method by extrusion molding, etc.) remains in the film. Therefore, the dimensional change rate exceeds 1.0%. By adjusting the thickness of the film, the heat treatment conditions of the film, and the winding conditions of the film, each dimensional change rate can be converged to a predetermined range. This can improve the dimensional stability after the long laminate is processed after the conductive metal layer is formed to form a circuit.

[0055] Such a long laminate of the present invention has, in this order, the present film 1 and a conductive metal layer. The conductive metal layer preferably includes a metal seed layer and a metal layer, and more preferably is formed only of a metal seed layer and a metal layer. Such a long laminate also has the present film 1 composed of the F polymer and has excellent physical properties such as heat resistance and electrical properties, and is therefore useful as an electronic substrate material for printed wiring boards (particularly flexible printed wiring boards). A printed wiring board manufactured from such a long laminate has, in that order, a transmission circuit formed from a conductive metal layer and an F polymer layer, and since the F polymer layer is formed from this film 1 containing small-sized spherulites, it has excellent plating heat resistance and is less likely to peel off from the transmission circuit and the F polymer layer.

[0056] The long film according to the second embodiment of the present invention (hereinafter also referred to as "this film 2") is composed of a polymer containing TFE units (hereinafter also referred to as "F polymer II") with an MFR of 5 to 40 g / 10 min. This film 2 is heated at 180°C for 30 minutes to measure the thermal expansion rate. When the thermal expansion rate in a first direction, which forms an angle of 45° with the machine direction (MD direction), is defined as A [%], and the thermal expansion rate in a second direction perpendicular to the first direction is defined as B [%], each of A and B is -2 to +1%, and |AB| is 1% or less. The long laminate obtained by laminating this film 2 and a long metal foil as a long substrate can be suitably used as a printed wiring board by cutting it to a predetermined length and processing the metal foil into a transmission circuit (including vias).

[0057] The present film 2, whose thermal expansion coefficients A and B in two oblique directions (directions inclined to the flow direction) and their difference (absolute value: |AB|) are within the above ranges, has small distortion in the oblique directions and is sufficiently uniform. Therefore, when the present film 2 is used to manufacture a long laminate, wrinkles are unlikely to occur in the oblique directions, and a high yield can be maintained. In addition, it is considered that the distortion in the diagonal direction is small and sufficiently uniform even in the long laminate. Therefore, it is considered that such a long laminate has excellent thermal shock resistance, and the deformation in the diagonal direction during processing is suppressed. For example, when the long laminate of the present invention in which the metal foil is a long substrate is processed into a printed wiring board, the thermal shock resistance during the formation of a through hole or a via is high, and as a result, a printed wiring board that is less likely to break is easily obtained.

[0058] The thermal expansion and contraction rates A and B of the film 2 in the oblique directions are measured as follows. First, a square sample with a length of 12 cm and two sides along the flow direction (longitudinal direction, MD) and two sides along the width direction (transverse direction, TD) is cut out from the film 2. Then, a line segment with a length of 10 cm is drawn on each diagonal of the surface of the obtained sample. Next, the sample is heated in an oven at 180°C for 30 minutes, then removed, and the length of the line segments drawn on the diagonal is measured again. The thermal expansion rates A and B are values ​​calculated according to the formula: {(length of the line segment before heating)-(length of the line segment after heating)} / (length of the line segment before heating) x 100. In other words, the thermal expansion rates A and B are the rate of change (percentage) in the length of the line segment before and after heating. Note that a negative value indicates a contraction of the present film 2, and a positive value indicates an expansion of the present film 2. The thermal expansion / contraction rates A and B are each preferably -2.0 to +0.5%, and more preferably -1.5% or more and less than 0%. The difference therebetween (|AB|) is preferably 0.8% or less, and more preferably 0.5% or less. If the thermal expansion / contraction rates A and B and the difference therebetween are within the above ranges, the present film 2 is less likely to develop wrinkles due to non-uniform oblique distortion even when heated.

[0059] The F polymer II in the present film 2 is a heat-fusible tetrafluoroethylene polymer having a predetermined MFR. The MFR of the F polymer II is 5 to 40 g / 10 min, preferably 10 to 30 g / 10 min, and more preferably 15 to 30 g / 10 min. In this case, the oblique distortion of the produced present film 2 is unlikely to remain, and the thermal shock resistance is sufficiently increased. The melting temperature of the F polymer II is preferably 200 to 320° C. In this case, the MFR can be easily adjusted to a desired range.

[0060] F polymer II is a polymer containing TFE units, and may be a homopolymer of TFE or a copolymer of TFE and other comonomers.F polymer II may be used alone or in combination of two or more kinds. As the F polymer II in the present film 2, a polymer having a TFE unit and a unit based on hexafluoropropylene (HFP) (HFP unit), a unit based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE unit), or a unit based on fluoroalkylethylene (FAE) (FAE unit) (hereinafter collectively referred to as "PAE unit" is preferable. In addition, as the F polymer II, a polymer having a polar functional group introduced into the above polymer is more preferable.

[0061] The polar functional group is preferably a hydroxyl group-containing group, a carbonyl group-containing group, an acetal group or a phosphono group (-OP(O)OH2), and more preferably a carbonyl group-containing group. The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, and more preferably -CF2CH2OH, -C(CF3)2OH or a 1,2-glycol group (-CH(OH)CH2OH). The carbonyl group-containing group is a group containing a carbonyl group (>C(O)), and is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.) or a carbonate group (-OC(O)O-).

[0062] From the viewpoint of enhancing adhesion to a substrate such as a metal foil, the polymer F II is preferably a polymer having a hydroxyl group-containing group or a carbonyl group-containing group. Methods for introducing a polar functional group into F polymer II include a method of copolymerizing TFE with a monomer having a polar functional group (hereinafter also referred to as a "polar monomer"), and a method of subjecting F polymer II to a plasma treatment or corona treatment. Examples of F polymers II having polar functional groups include polymers having units based on polar monomers (hereinafter also referred to as "polar units") and TFE units, and polymers into which carbonyl- or hydroxyl-containing groups have been introduced by plasma treatment, corona treatment, or the action of a polymerization initiator or chain transfer agent.

[0063] The F polymer II having a polar functional group is preferably a polymer having a TFE unit and a polar unit, more preferably a polymer having a TFE unit, a PAE unit and a polar unit. Of all the units constituting the F polymer II, the proportion of TFE units, the proportion of PAE units and the proportion of polar units are preferably 90 to 99 mol %, 1 to 10 mol % and 0 to 3 mol %, respectively.

[0064] The PAE unit is preferably a PAVE unit or an HFP unit, more preferably a PAVE unit. The PAE unit may be of two or more types. Examples of PAVE include CF2=CFOCF3 (PMVE), CF2=CFOCF2CF3, CF2=CFOCF2CF2CF3 (PPVE), CF2=CFOCF2CF2CF2CF3, and CF2=CFO(CF2)8F, with PMVE or PPVE being preferred. FAEs include CH2=CH(CF2)2F(PFEE), CH2=CH(CF2)3F, CH2=CH(CF2)4F(PFBE), CH2=CF(CF2)3H, and CH2=CF(CF2)4H. Examples of the polar monomer include itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride (also known as himic anhydride; hereinafter also referred to as "NAH"), and maleic anhydride.

[0065] The present film 2 may contain resins and other components other than F polymer II within the range that does not impair the effects of the present invention. However, the amount of F polymer II contained in the present film 2 is preferably 90 mass % or more, more preferably 100 mass %. The embodiments of the resins and other components other than the F polymer are similar to those of the present film 1 other than the F polymer.

[0066] The present film 2 can be produced by a die coating method (a melt extrusion method using a T-die) from the viewpoint of being able to adjust the distortion (particularly the distortion in the oblique direction). The present inventors have found that the oblique distortion of a long film by the die coating method depends on the state (temperature, fluidity) of the molten F polymer II and the cooling conditions, and is determined by the state of the molten F polymer II discharged from the T-die until it is crystallized by the cooling roll. In other words, the present inventors have found that, by appropriately setting the state of the F polymer II and the cooling conditions and controlling the crystallization of the F polymer II, the oblique distortion of the obtained film 2 (thermal expansion and contraction rates A, B and the difference between them) will converge to a predetermined range.

[0067] The long film manufacturing method of the present invention (hereinafter also referred to as "Method 3") is a method of manufacturing the present film 2 by a die coating method, in which F polymer II is extruded in a molten state from a die, and the molten F polymer II is heated in a non-contact heating section before it comes into contact with the first cooling roll. 1 is also a schematic diagram showing one embodiment of a long film manufacturing apparatus used in Method 3. The names and roles of the components in FIG. 1 are the same as those described in Method 1. According to this configuration, the molten F polymer II discharged from the T-die 20 is maintained at a high temperature by heating with the heater 80 even while reaching the first cooling roll 30. Therefore, the molten F polymer II flowing down toward the first cooling roll 30 maintains a relatively high fluidity, and is unlikely to be stretched due to its own weight or the tensile force of the first cooling roll 30. As a result, it is presumed that the occurrence of the bowing phenomenon (diagonal orientation of the F polymer II) is suppressed when the molten F polymer II is made into a film, and a long film with small distortion in the diagonal direction (thermal expansion and contraction rates A, B, and the difference between them) as described above was obtained. 1, the F polymer II discharged from the T-die 20 is heated by the heater 80 from both sides in the thickness direction, so that the temperature uniformity in the thickness direction is high, and the effect of suppressing the occurrence of the bowing phenomenon is excellent. From the viewpoint of further improving the effect of suppressing the occurrence of the bowing phenomenon, it is preferable to configure the heater 80 so that the temperature of the F polymer II in the width direction can be made uniform. In this case, for example, the width of the heater 80 may be designed to be sufficiently larger than the length of the F polymer in the width direction.

[0068] When the temperature of the F polymer II in the T-die 20 is defined as X [°C] and the temperature of the heater 80 is defined as Z [°C], the difference therebetween (absolute value: |XZ|) is preferably 70°C or less, more preferably 30 to 50°C. In this case, the temperature of the F polymer II can be maintained sufficiently high until it reaches the first cooling roll 30 while preventing deterioration of the F polymer II. On the other hand, when the temperature of the F polymer II in the T die 20 is defined as X [°C] and the temperature of the first cooling roll 30 is defined as Y [°C], the difference (XY) is preferably 250°C or less, more preferably 200°C or less, and even more preferably 125 to 175°C. In this case, the degree of cooling of the F polymer II by the first cooling roll 30 becomes more appropriate, so that oblique distortion is less likely to remain in the obtained long film 1 (present film 2), and deformation due to insufficient cooling can also be suitably prevented. Specifically, Y is appropriately set according to X, and is preferably 150 to 250°C.

[0069] In addition, from the viewpoint of further improving the effect of suppressing the occurrence of the bowing phenomenon during cooling by the first cooling roll 30, it is preferable to configure the first cooling roll 30 so that the temperature of the F polymer II can be made uniform in the width direction. Therefore, the first cooling roll 30 is preferably configured to have a mechanism for passing a heat medium, and is preferably configured to have a dual mechanism for repeatedly passing the heat medium back and forth in the axial direction. The temperature Y of the first cooling roll 30 means the temperature of the heat medium. The thickness (thickness t in FIG. 1) of the F polymer II in a molten state before contacting the first cooling roll 30 is preferably 5 to 150 μm, more preferably 10 to 100 μm. In this case, the accuracy of heating by the heater 80 and cooling by the first cooling roll 30 is improved, and the resulting long film 1 is less likely to have oblique distortion.

[0070] If the ratio of the opening of the lip 21 of the T-die 20 to the thickness of the final long film 1 (draw ratio) is large, the molecular chains of the polymer contained in the F polymer II are strongly stretched, and the polymer molecules tend to be oriented. As a result, the oblique distortion remaining in the long film 1 tends to be large. Therefore, the draw ratio is preferably 50 or less. The peripheral speed of the first cooling roll 30 (peripheral speed S in FIG. 1) is also preferably 1 to 25 m / min, and more preferably 2 to 20 m / min, from the viewpoint of further reducing oblique distortion remaining in the long film 1. The temperature of the second cooling roll 40 is preferably 50 to 100°C, and more preferably 30 to 80°C.

[0071] The F polymer II (present film 2) after being separated from the first cooling roll 30 may be subjected to a surface treatment capable of introducing adhesive functional groups onto the surface. Examples of such surface treatments include discharge treatments such as corona discharge treatment and plasma treatment, plasma graft polymerization treatment, light irradiation treatments such as electron beam irradiation and excimer UV light irradiation, itro treatment using a flame, and wet etching treatment using metallic sodium. This surface treatment introduces polar functional groups such as hydroxyl groups, carbonyl groups, and carboxyl groups onto the surface of the long film 1, thereby improving adhesion to other surfaces.

[0072] 1, a pair of heaters 80 are arranged, but only one may be arranged. The non-contact heating section may be configured with a blower device that blows hot air instead of the heater 80. Two first cooling rolls 30 may be arranged opposite each other, and the molten F polymer II may be passed between them to be cooled, or the outer first cooling roll 30 of the two first cooling rolls 30 may be omitted to be cooled.

[0073] The film 2 can be used to produce a long laminate. The method for producing a long laminate of the present invention (hereinafter also referred to as "Method 4") is a method in which the present film 2 and a long substrate are laminated at a temperature of 25 to 100°C to obtain a long laminate having the present film 2 and the long substrate in this order. The definition and scope of the long laminate and the method for producing the long laminate using the present film 2, including their preferred embodiments and uses, are the same as those using the present film 1 in the present method 2.

[0074] The long film, the method for producing the long film, the method for producing the long laminate, and the long laminate of the present invention have been described above, but the present invention is not limited to the configurations of the above-mentioned embodiments. For example, the long film and long laminate of the present invention may each have any other configuration in addition to the configuration of the above embodiment, or may be replaced with any configuration that exhibits a similar function. In addition, the long film manufacturing method and long laminate manufacturing method of the present invention may each have any other process in addition to the configuration of the above embodiment, or may be replaced with any process that produces a similar effect. EXAMPLES

[0075] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. 1. Manufacturing and Evaluation Examples (Part 1) 1-1.F Polymer F Polymer 1A: A polymer containing 98.0 mol% TFE units and 2.0 mol% PPVE units, in that order, and having no polar functional groups (melting point: 305°C) F Polymer 1B: A polymer containing 98.0 mol%, 1.9 mol%, and 0.1 mol% of TFE units, PPVE units, and NAH units, in that order, and having a polar functional group (melting point: 300°C, MFR: 20g / 10min) F Polymer 1C: A polymer containing 98.7 mol% TFE units and 1.3 mol% PPVE units, in that order, and having no polar functional groups (melting point: 305°C) F Polymer 1D: A polymer containing 85.0 mol% TFE units and 15.0 mol% PMVE units, in that order, and having no polar functional groups (melting point: 285°C)

[0076] 1-2.Long film 1-2-1. Manufacturing of long films (Long Film 11) F polymer 1A was fed into an extruder (350°C) connected to a T-die of the manufacturing apparatus shown in Figure 1, and extruded (discharged) from a T-die with a width of 800 mm. The temperature of F polymer 1A in the T-die was set to 350°C. The opening of the lip of the T-die was set to 0.75 mm. Two ceramic heaters were installed vertically below the T-die and their temperatures were set to 400°C. A heat medium circulating metal roll was used for each of the pair of first cooling rolls, and the temperature of the heat medium was set to 80° C. The peripheral speed of the first cooling roll was set to 15 m / min. After being removed from the first cooling roll, one side of the F polymer was subjected to a discharge rate of 30 W·min / m 2 The film was subjected to a corona discharge treatment at 600 V for 2 hours to obtain a long film 11 having a thickness of 25 μm (draw ratio of 30) and a width of 500 mm.

[0077] (Long Film 12) A continuous film 12 was obtained in the same manner as in the continuous film 11, except that F polymer 1B was used instead of F polymer 1A. (Long Film 13) A continuous film 13 was obtained in the same manner as the continuous film 11, except that a mixture of 80 parts by mass of F polymer 1C and 20 parts by mass of F polymer 1D was used instead of F polymer 1A. (Long film 14 (Comparative example)) A long film 14 was obtained in the same manner as for the long film 11, except that the ceramic heater was omitted.

[0078] 1-2-2. Measurement of spherulite radius For each long film, a polymer phase structure analysis system using small-angle light scattering (Otsuka Chemical Co., Ltd., "PP-1000") was used to measure the scattering vector q (μm -1 The spherulite radius was measured by correlating the scattering intensity (Is) with the scattering intensity (Is). If the scattering vector at which the scattering intensity is the highest is qmax, then qmax = (4πn / λ0) × sin(θmax / 2) [where λ0 is the wavelength of light in a vacuum, n is the refractive index of the medium, and θmax is the scattering angle at the position where the scattering intensity peaks.], which leads to the spherulite radius R (μm) = 4.09 / qmax.

[0079] 1-2-3. Haze measurement For each long film, the haze (turbidity) was measured using a haze meter (manufactured by Suga Test Instruments Co., Ltd., "HZ-2") in accordance with JIS K 7361-1: 1997. Note that the light source used was a C light source.

[0080] 1-3. Manufacturing of temporary long laminates Using the manufacturing apparatus shown in Figure 3, a long film 11 was laminated on both sides of a 50 μm thick heat-resistant resin film (manufactured by Toray DuPont, "Kapton 200EN") under the following conditions to produce a three-layer temporary long laminate 11. The surface temperature (lamination temperature) of the pair of laminating rolls (metal rolls) was set to 60° C. The pressure applied by the laminating rolls was set to 15 kN / m, and the conveying speed (laminating speed) of the polyimide film and the long film 11 was set to 3 m / min. The tension applied to the polyimide film was set to 200 N, and the tension applied to the long film 11 was set to 20 N. Temporary long laminates 12 to 14 were obtained in the same manner as for the temporary long laminate 1, except that the long films 12 to 14 were used instead of the long film 11, respectively.

[0081] 1-4-1. Manufacturing of this long laminate Using the manufacturing apparatus shown in FIG. 3, two long copper foils (manufactured by Fukuda Metal Foil and Powder Co., Ltd., "CF-T49A-DS-HD2-12", thickness: 12 μm, Rzjis: 1.2 μm) were laminated under the following conditions so that the copper foils were in contact with the long film 11 of the temporary long laminate 11, thereby obtaining the actual long laminate 11. The surface temperature (lamination temperature) of the pair of laminating rolls (metal rolls) was 360° C. The pressure applied by the laminating rolls was 5 kN / m, and the conveying speed (laminating speed) of the copper foil and the temporary long laminate was 1 m / min. The permanent long laminates 12 to 14 were obtained in the same manner as the permanent long laminate 1, except that the temporary long laminates 12 to 14 were used instead of the temporary long laminate 11, respectively.

[0082] 1-4-2. Evaluation of solder heat resistance A 5 cm square sample was cut out from each long laminate, and the sample was floated five times in a solder bath at 288° C. for 10 seconds. Thereafter, the appearance of the sample was visually inspected and evaluated according to the following evaluation criteria. [Evaluation Criteria] ◯ (Fair): No visible expansion or peeling of the sample. × (Fail): Expansion or peeling was observed in the sample. The results obtained are summarized in Table 1 below.

[0083] [Table 1]

[0084] FIG. 4 is a photograph of the surface of the long film 12 observed with a polarizing microscope. Since the spherulite radius of the long film 12 is small, the spherulites are densely present and the surface irregularities are small. Therefore, it is considered that the irregularities present on the surface of the long film 12 are filled in during the temporary lamination, and the expansion and peeling of this long laminate due to high-temperature soldering are suppressed.

[0085] 1-5-1. Manufacturing of long laminates (part 2) In a roll-to-roll continuous process, the surface of the long film 11 was plasma treated (treatment pressure: vacuum degree 30 Pa, treatment gas: argon gas (flow rate: 950 sccm) and hydrogen gas (flow rate: 50 sccm), treatment power: 3 kW, treatment time: 40 seconds). A seed layer was formed by sputtering using a vapor phase growth method on the plasma-treated surface of the long film 11. Sputtering was performed twice, with the first target metal being a nickel-chromium alloy and the layer formed to a thickness of 10 nm, and the second target metal being copper and the layer formed to a thickness of 100 nm. A copper layer (thickness: 12 μm) was formed on the surface of the seed layer formed on the long film 11 by electrolytic plating using copper sulfate, to obtain a long film 11 (long laminate 1I) having a conductive metal layer on the surface. A long laminate 1II was obtained from the long film 12, a long laminate 1III was obtained from the long film 13, and a long laminate 1IV was obtained from the long film 14 in the same manner as the long laminate 1I, except that the type of long film was changed.

[0086] 1-5-2.Evaluation of conductivity For each of the long laminates 1I to 1IV, 100 transmission circuits (width: 50 μm, length: 100 mm) were formed on the conductive metal layer, and the resistance value at both ends of each circuit was measured to evaluate the conductivity according to the following evaluation criteria. [Evaluation Criteria] 〇 (Good): The resistance value of all transmission circuits (100 circuits) is less than 10 Ω. △(Acceptable): There are 1 to 4 transmission circuits with a resistance value of 10 Ω or more. × (Not possible): There are five or more transmission circuits with a resistance value of 10 Ω or more. The results obtained are summarized in Table 2 below.

[0087] [Table 2]

[0088] The long laminate 1IV is formed from a polymer film (long film 14) with a large radius of spherulites, and since breaks are likely to occur at the interface between the transmission circuits and the polymer spherulites, it is believed that many of the transmission circuits have high resistance values.

[0089] 2. Manufacturing and Evaluation Examples (Part 2) 2-1.F polymer F Polymer 2A: A copolymer containing 98.0 mol% TFE units and 2.0 mol% PPVE units, in that order, and having no polar functional groups (melting point: 305°C, MFR: 25g / 10min) F Polymer 2B: A copolymer containing 98.0 mol%, 1.9 mol%, and 0.1 mol% of TFE units, PPVE units, and NAH units, in that order, and having polar functional groups (melting point: 300°C, MFR: 20g / 10min) F Polymer 2C: A copolymer containing 98.0 mol% TFE units and 2.0 mol% PPVE units, in that order, and having no polar functional groups (melting point: 305°C, MFR: 5g / 10min)

[0090] 2-2.Long film 2-2-1. Manufacturing of long films (Long Film 21) In the manufacturing apparatus shown in Figure 1, an apparatus was used in which the outer first cooling roll of the two first cooling rolls was omitted, F polymer 2A was used instead of F polymer 1A, and the temperature of the heat transfer medium of the first cooling roll was set to 200°C. In the same manner as in 1-2-1, a long film 21 (MFR: 27 g / 10 min) having a thickness of 25 μm (draw ratio 30) and a width of 500 mm was obtained.

[0091] (Long Film 22) A long film 22 (MFR: 18 g / 10 min) was obtained in the same manner as the long film 21, except that F polymer 2B was used instead of F polymer 2A. (Long Film 23) A continuous film 23 was obtained in the same manner as the continuous film 21, except that F polymer 2C was used instead of F polymer 2A. (Long Film 24) A continuous film 24 was obtained in the same manner as the continuous film 21, except that the opening of the lip of the T-die was set to 1.5 mm (draw ratio 60). (Long film 25 (Comparative example)) A long film 25 was obtained in the same manner as the long film 21, except that the ceramic heater was omitted.

[0092] 2-2-2.Evaluation of long films A square sample with 12 cm sides was cut from the end of the width direction of the obtained long film, with two sides along the flow direction and two sides along the width direction. Then, lines 10 cm long were drawn on the diagonal lines of the surface of the obtained sample. Next, the sample was placed in an oven at 180°C for 30 minutes and heated, then removed, and the length of the lines drawn on the diagonal lines was measured again, and the thermal expansion coefficients A and B in the oblique directions were calculated.

[0093] 2-3. Temporary long laminate 2-3-1. Manufacturing of temporary long laminates Using the manufacturing apparatus shown in FIG. 2, a long copper foil and a long film 21 were laminated under the following conditions to manufacture a temporary long laminate 21 having a two-layer structure. The surface temperature (lamination temperature) of the pair of laminating rolls (metal rolls) was set to 60° C. The pressure applied by the laminating rolls was set to 15 kN / m, and the conveying speed (laminating speed) of the copper foil and the long film 21 was set to 3 m / min. The tension applied to the copper foil was set to 200 N, and the tension applied to the long film 21 was set to 20 N. Temporary long laminates 22 to 25 were obtained in the same manner as the temporary long laminate 21, except that the long films 22 to 25 were used instead of the long film 21, respectively.

[0094] 2-3-2. Evaluation of temporary long laminate The obtained provisional long laminate was visually inspected for the presence or absence of wrinkles, and was evaluated according to the following evaluation criteria. [Evaluation Criteria] ◯ (Good): No wrinkles were observed in the temporary long laminate. △ (Fair): The long film before lamination had some slack in the diagonal direction, but no wrinkles were observed in the temporary long laminate. × (unacceptable): Diagonal wrinkles were observed in the temporary long laminate.

[0095] 2-4. This long laminate 2-4-1. Manufacturing of this long laminate Using the manufacturing apparatus shown in Figure 3, two temporary long laminates 21 were laminated onto a polyimide film (heat-resistant resin film) under the following conditions so that the long films 21 were in contact with both sides of the polyimide film, thereby obtaining the actual long laminate 21. The surface temperature (lamination temperature) of the pair of laminating rolls (metal rolls) was 360° C. The pressure applied by the laminating rolls was 5 kN / m, and the conveying speed (laminating speed) of the temporary long laminate 21 and the polyimide film was 1 m / min. The permanent long laminates 22 to 25 were obtained in the same manner as the permanent long laminate 21, except that the temporary long laminates 22 to 25 were used instead of the temporary long laminate 21, respectively.

[0096] 2-4-2. Evaluation of this long laminate The dimensional stability test of the obtained long laminate was carried out in accordance with JIS C 6481:1996. A square sample having two sides along the flow direction and two sides along the width direction and measuring 30 cm on each side was cut out from an end in the width direction of this long laminate. A 25 cm long line was drawn on each of the diagonal lines (the 45° direction, which is at an angle of 45° with respect to the flow direction, and the 135° direction, which is perpendicular to this 45° direction) on the surface of this sample, and punched holes were formed with their centers at both ends of each line. After that, the two copper foils were removed from the sample by etching with an aqueous solution of iron chloride. The distance between the centers of the two punched holes located on each diagonal line was measured before and after etching, and the expansion and contraction rate of the sample in the diagonal direction after etching was calculated. Furthermore, the sample was heated in a hot air circulating oven at 150°C for 30 minutes, and then cooled to 25°C. The distance between the centers of two punched holes located on each diagonal line was measured again to determine the diagonal expansion rate after heating. The diagonal expansion rate of the sample after heating is a value based on the distance between the centers of the two punched holes before etching.

[0097] 2-5.Printed wiring boards 2-5-1. Manufacturing of printed wiring boards Using this long laminate 21, a sample for a thermal shock test of copper-plated through holes was produced as a printed wiring board 21 according to the method specified in JIS C 5016:1994. The through holes had a diameter of 100 μm and a land diameter of 300 μm. The through holes were formed using a UV laser processing machine (Esi5330). Except for using the long laminates 22 to 25 instead of the long laminate 21, samples for thermal shock resistance test were obtained as printed wiring boards 22 to 25 in the same manner as for printed wiring board 21.

[0098] 2-5-2. Evaluation of printed wiring boards The obtained sample was subjected to a thermal shock test using a thermal shock tester (manufactured by Espec Corp., "TSE-11-A"), in which the sample was repeatedly cooled and heated at -65°C for 30 minutes and heated at 125°C for 30 minutes as one cycle. The resistance between the ends of the vias (copper plated) in the through holes was constantly measured using a four-terminal electrode voltmeter (HIOKI E.E. CORPORATION, "Milliohm HiTester 3540"), and the number of cycles in which the resistance value changed by ±10% or more of the initial value (number of cycles to breakage) was confirmed. The results obtained are summarized in Table 3 below.

[0099] [Table 3] [Industrial Applicability]

[0100] The long laminate of the present invention can be suitably used for printed wiring boards (particularly flexible printed wiring boards), electromagnetic wave shielding sheets, exterior bodies for lithium ion batteries, and the like. [Explanation of symbols]

[0101] 1...long film, 2...long substrate, 3...second long substrate, 4...heat-resistant resin film, 10...manufacturing device, 20...T-die, 21...lip, 30...first cooling roll, 40...second cooling roll, 50...winding roll, 61, 62...transport roll, 70...nip roll, 80...heater, 100, 200...manufacturing device, 101...laminating roll, 103...first delivery roll, 105...second delivery roll, 107...third delivery roll, t...thickness, S...circumferential speed, T1, T2, T3...temperature, L, M, N...long laminate

Claims

1. A long film is composed of a heat-fusible polymer containing a first unit based on tetrafluoroethylene, a second unit based on perfluoro(alkyl vinyl ether), and a third unit based on itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, or maleic anhydride, and contains spherulites of the heat-fusible polymer, the spherulites having a radius of 10 μm or less.

2. The long film according to claim 1, wherein the heat-fusible polymer contains 2 to 4 mol % of units based on perfluoro(propyl vinyl ether) as the second units.

3. The long film according to claim 1 or 2, wherein the heat-fusible polymer has a ratio of the first unit of 90 to 99 mol%, a ratio of the second unit of 0.5 to 9.97 mol%, and a ratio of the third unit of 0.01 to 3 mol%.

4. The long film according to any one of claims 1 to 3, wherein the melt flow rate of the heat-fusible polymer is 5 to 40 g / 10 min.

5. The long film according to any one of claims 1 to 4, wherein the haze of the long film having a thickness of 50 μm is 1 to 5%.

6. A method for producing a long laminate, comprising laminating the long film according to any one of claims 1 to 5 and a long substrate at a temperature of 25 to 100°C to obtain a long laminate having the long film and the long substrate in this order.

7. A long laminate comprising the long film according to any one of claims 1 to 5 and a conductive metal layer in this order.

8. A heat-fusible polymer comprising a first unit based on tetrafluoroethylene and a second unit based on perfluoro(alkyl vinyl ether), said heat-fusible polymer The method for producing a long film by a die coating method includes extruding the heat-fusible polymer in a molten state from a die, and heating the molten heat-fusible polymer in a non-contact heating section before the polymer comes into contact with a first cooling roll.

9. The method according to claim 8, wherein when the temperature of the heat-fusible polymer in the die is defined as X and the temperature of the first chill roll is defined as Y, X-Y is 230° C. or higher.

10. The method according to claim 8 or 9, wherein |X-Z| is 70° C. or less, where X is the temperature of the heat-fusible polymer in the die and Z is the temperature of the non-contact heating part.

11. A long film made of a tetrafluoroethylene-based polymer containing units based on itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride or maleic anhydride and having a melt flow rate of 5 to 40 g / 10 min, wherein the long film is heated at 180° C. for 30 minutes to measure its thermal expansion / contraction rate, and when the thermal expansion / contraction rate in a first direction that forms an angle of 45° with the flow direction is defined as A and the thermal expansion / contraction rate in a second direction perpendicular to the first direction is defined as B, each of A and B is −2 to +1%, and |A−B| is 1% or less.

12. The tetrafluoroethylene-based polymer has a unit based on tetrafluoroethylene, a PAE unit, and a unit based on a polar monomer, the PAE units are hexafluoropropylene-based units, perfluoro(alkyl vinyl ether)-based units or fluoroalkylethylene-based units; the unit based on a polar monomer is a unit based on itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride or maleic anhydride; The long film according to claim 11, wherein the ratio of the units based on tetrafluoroethylene is 90 to 99 mol%, the ratio of the PAE units is 1 to 10 mol%, and the ratio of the units based on the polar monomer is more than 0 mol% and 3 mol% or less among all the units constituting the tetrafluoroethylene-based polymer.

13. A method for producing a long laminate, comprising laminating the long film according to claim 11 or 12 and a long substrate at a temperature of 25 to 100° C. to obtain a long laminate having the long film and the long substrate in this order.

14. A method for producing a long film made of a tetrafluoroethylene-based polymer having a melt flow rate of 5 to 40 g / 10 min, the long film being heated at 180° C. for 30 minutes and thermal expansion / contractions measured, the thermal expansion / contractions in a first direction which forms an angle of 45° with the flow direction being defined as A, and the thermal expansion / contractions in a second direction perpendicular to the first direction being defined as B, wherein A and B are each -2 to +1%, and |A-B| is 1% or less, by a die coating method, the method comprising the steps of: extruding the tetrafluoroethylene-based polymer in a molten state from a die, and heating the molten tetrafluoroethylene-based polymer in a non-contact heating section before it comes into contact with a first cooling roll.

15. The manufacturing method according to claim 14, wherein |X-Z| is 70° C. or less, where X is the temperature of the tetrafluoroethylene-based polymer in the die and Z is the temperature of the non-contact heating part.

Citation Information

Patent Citations

  • Modified fluororesin and molded form

    JP1999116623A

  • Flame-retardant polyamide stretched film

    JP2014091806A

  • Long-sized laminate for high frequency circuit board, and method for manufacturing the same

    JP2016087799A

  • Spherulite-micronizing agent for crystalline fluororesin and crystalline fluororesin composition containing the micronizing agent

    WO1999062999A1

  • Method for manufacturing laminated body, laminated body, and method for manufacturing flexible printed board

    WO2019008876A1